Analysis of Factors Affecting E-Loyalty in Online Media Case Studies Tribun Kaltim - Mayasanto, Ade; Prihanto, Y Johny Natu; Sudiyono, Kristianus Ade (ADI Publisher, 2021)
Online-based media in Indonesia continues to grow. Much online press makes traffic an advertising business. The more reader traffic, the greater the revenue earned. The study aimed to look at how reader loyalty in online media. The central premise is to answer the factors that affect reader loyalty in online media. The research methodology uses the survey method. The survey took place in TribunKaltim with a total sample of 201 respondents. The research data was processed using Smart Pls tools. Results showed a positive correlation and significant influence of e-trust and e-satisfaction on e-loyalty readers in online media. The positive correlation and considerable impact of e-trust and e-satisfaction are inseparable from Fulfillment or reliability and online web media design. The practical implication of this research, management considerations to improve e-trust, e-satisfaction dan e-loyalty customers of online media.